Modeling Fetal Alcohol Spectrum Disorder: Validating an Ex Vivo Primary Hippocampal Cell Culture System. (10th May 2016) - Tunc‐Ozcan, Elif; Ferreira, Adriana B.; Redei, Eva E.
Abstract : Background: Fetal alcohol spectrum disorder (FASD) is the leading nongenetic cause of mental retardation. There are no treatments for FASD to date. Preclinical in vivo and in vitro studies could help in identifying novel drug targets as for other diseases. Here, we describe an ex vivo model that combines the physiological advantages of prenatal ethanol (EtOH) exposure in vivo with the uniformity of primary fetal hippocampal culture to characterize the effects of prenatal EtOH. The insulin signaling pathways are known to be involved in hippocampal functions. Therefore, we compared the expression of insulin signaling pathway genes between fetal hippocampi (in vivo) and primary hippocampal culture (ex vivo). The similarity of prenatal EtOH effects in these 2 paradigms would deem the ex vivo culture acceptable to screen possible treatments for FASD. Methods: Pregnant Sprague–Dawley rats received 1 of 3 diets: ad libitum standard laboratory chow (control‐C), isocaloric pair‐fed (nutritional control), and EtOH containing liquid diets from gestational day (GD) 8. Fetal male and female hippocampi were collected either on GD21 (in vivo) or on GD18 for primary culture (ex vivo). Transcript levels of Igf2, Igf2r, Insr, Grb10, Rasgrf1, and Zac1 were measured by reverse transcription quantitative polymerase chain reaction. Results: Hippocampal transcript levels differed by prenatal treatment in both males and females with sex differences observed in the expression of Igf2 and Insr . The effect of prenatal EtOH on the hippocampal expression of the insulin pathway genes was parallel in the in vivo and the ex vivo conditions. Conclusions: The similarity of gene expression changes in response to prenatal EtOH between the in vivo and the ex vivo conditions ascertains that these effects are already set in the fetal hippocampus at GD18. This strengthens the feasibility of the ex vivo primary hippocampal culture as a tool to test and screen candidate drug targets for FASD. Abstract : Hippocampal primary neuronal cultures were established from gestational day 18 fetuses whose mother consumed ethanol, pair‐fed, or normal control diets. There were no differences in developmental stage or morphology due to the prenatal treatments in these cultures. These ex vivo hippocampal neuronal cultures showed gene expression profiles that paralleled those obtained from gestational day 21 fetal hippocampi receiving the same prenatal treatments suggesting the ex vivo model applicable to screen candidate drug targets for FASD.